Clinical learning environment: Lived experiences of post-basic critical care nursing students - Helen Hattingh; Charlené Downing (Elsevier, 2020)
Background: Quality clinical placement and rotation of post-basic critical care nursing students to different critical care clinical learning environments is aimed at enabling theory-practice integration. Students are expected to develop critical thinking and problem-solving skills through interaction with competent expert critical care qualified nurses. Post-basic critical care students enter the critical care clinical learning environments and expect to be supported in positive practice environments. Aim: To explore and describe the lived experiences of post-basic critical care nursing students of their clinical learning environment. Design: A qualitative exploratory descriptive and contextual design. Methods: A descriptive phenomenological approach was followed. Five focus group interviews were conducted. 18 Purposively sampled post-basic critical care nursing students participated. Giorgi's qualitative data analysis method was used. Results: Three themes emerged: Post-basic critical care nursing students experienced 1) stress in terms of the rapid adjustments they had to make in ever-changing environments and attitudes; 2) Learning challenges that lead to concerns of whether they would be able to reach clinical objectives, and 3) Self-growth and mastery of the skill of assertiveness through perseverance. Conclusions: Clinical learning and understanding of critical care nursing students are shaped by the way they are regarded, welcomed and supported in critical care clinical learning environments. A culture of care and value for learning and learning support and actions focussed on facilitating rapid adjustment to new environments are recommended to enhance the positive experiences and professional development of post-basic critical care nursing students in the critical care clinical learning environment.